2015
DOI: 10.7717/peerj.1337
|View full text |Cite
|
Sign up to set email alerts
|

Gluten-free food database: the nutritional quality and cost of packaged gluten-free foods

Abstract: Notwithstanding a growth in popularity and consumption of gluten-free (GF) food products, there is a lack of substantiated analysis of the nutritional quality compared with their gluten-containing counterparts. To put GF foods into proper perspective both for those who need it (patients with celiac disease) and for those who do not, we provide contemporary data about cost and nutritional quality of GF food products. The objective of this study is to develop a food composition database for seven discretionary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
119
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(154 citation statements)
references
References 44 publications
11
119
0
8
Order By: Relevance
“…The average fiber content is 5.19%, which is higher than in wheat breads, as also reported by Allen and Orfila (2018), and ranges from 0% to 11.7%. Other studies did not find differences in the fiber content of breads with and without gluten (Kulai & Rashid, 2014;Missbach et al, 2015), or showed a lower amount of fiber in GFBs (do Nascimento et al, 2014). Although mixtures of flours and starches used for GFBs present lower fiber content than wheat flour, the scarce differences should be related to the inclusion of hydrocolloids, nutritionally categorized as fibers, to mimic gluten functionality.…”
Section: Nutrition Factsmentioning
confidence: 92%
See 1 more Smart Citation
“…The average fiber content is 5.19%, which is higher than in wheat breads, as also reported by Allen and Orfila (2018), and ranges from 0% to 11.7%. Other studies did not find differences in the fiber content of breads with and without gluten (Kulai & Rashid, 2014;Missbach et al, 2015), or showed a lower amount of fiber in GFBs (do Nascimento et al, 2014). Although mixtures of flours and starches used for GFBs present lower fiber content than wheat flour, the scarce differences should be related to the inclusion of hydrocolloids, nutritionally categorized as fibers, to mimic gluten functionality.…”
Section: Nutrition Factsmentioning
confidence: 92%
“…Conversely, research on the cost or nutritional value of GFPs has been carried out, although usually focused on the products available in a single country with a reduced number of breads or brands analyzed. These studies were conducted in Italy (Mazzeo, Cauzzi, Brighenti, & Pellegrini, ; Morreale, Angelino, & Pellegrini, ), Austria (Missbach et al., ), Spain (Matos & Rosell, ; Miranda, Lasa, Bustamante, Churruca, & Simon, ), the United Kingdom (Allen & Orfila, ; Fry, Madden, & Fallaize, ), Brazil (do Nascimento et al., , ), Australia (Wu et al., ), or Canada (Kulai & Rashid, ).…”
Section: Introductionmentioning
confidence: 99%
“…Gluten-free products were more expensive than regular products by 2-518% 4 Missbach et al (8) Austria Cereal-based Supermarkets Gluten-free products were more expensive than regular products by 207-267% 5…”
Section: Quality Supermarkets Regular Supermarkets Budget Supermarketmentioning
confidence: 99%
“…Additionally, more recent data from the UK showed that GFP were at least four times more expensive than their regular alternatives . Finally, a recent study from Austria found that the cost of all analysed GFP was 205–267% higher than that of the conventional foods .…”
Section: Introductionmentioning
confidence: 99%
“…Dostępna w sprzedaży mąka kukurydziana, ryżowa i gryczana może jednak być zanieczyszczona glutenem na skutek np. przetwarzania w tym samym zakładzie zbóż bezglutenowych i glutenowych [47]. Dlatego najlepiej polecać chorym produkty z licencjonowanym znakiem przekreślonego kłosa, ponieważ są one kontrolowane przez organizacje chorych na celiakię.…”
Section: Dieta Bezglutenowaunclassified